2022
DOI: 10.1186/s12885-022-09756-1
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological and prognostic value of CXCR4 expression in patients with lung cancer: a meta-analysis

Abstract: Background The C-X-C chemokine receptor 4 (CXCR4) has been suggested to play an important role in several types of cancers and is related to biological behaviors connected with tumor progression. However, the clinical significance and application of CXCR4 in lung cancer remain disputable. Thus, we conducted a meta-analysis to investigate the impact of CXCR4 expression on survival and clinicopathological features in lung cancer. Methods Comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Moreover, the (quantified) intratumoral lesion variability among multiple observers was higher on FAPI-targeted PET/CT when compared with the present findings on SUV max for [ 68 Ga]pentixafor 35 . As a possible explanation, substantial and consistent CXCR4 upregulation has already been described in an ex vivo setting for both aggressive lung cancer and NEN 36,37 . As we also enrolled mainly those tumor types, those previous immunohistochemical findings may partially explain the high concordance rates of minimum 0.92 for TLs.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, the (quantified) intratumoral lesion variability among multiple observers was higher on FAPI-targeted PET/CT when compared with the present findings on SUV max for [ 68 Ga]pentixafor 35 . As a possible explanation, substantial and consistent CXCR4 upregulation has already been described in an ex vivo setting for both aggressive lung cancer and NEN 36,37 . As we also enrolled mainly those tumor types, those previous immunohistochemical findings may partially explain the high concordance rates of minimum 0.92 for TLs.…”
Section: Discussionsupporting
confidence: 65%
“…It was reported that high CXCR4 expression corresponds to bad prognosis for breast ( 88 ), lung ( 90 ) and colorectal ( 118 ) cancers contradicting TCGA-based findings ( Figures 3B, C ). It was recently reported that in advanced CD8 negative thyroid cancer, high expression of CXCR4 and its ligand CXCL12 (SDF-1) correlates with bad prognosis, thus contradicting to TCGA data ( 89 ).…”
Section: Expression Of Molecules Involved In the Ctc Cluster Formatio...mentioning
confidence: 83%
“…It was reported that high CXCR4 expression corresponds to bad prognosis for breast (88), lung (90) and colorectal (118) cancers Mechanisms of circulating tumor cells (CTC) cluster formation and their properties. Highlighted in green, the process of CTC clusters formation; Tumor cells can separate from adjacent cells with more mobile mesenchymal cells at the leading edge of the invasion and cells with more epithelial properties behind (4, 5).…”
Section: Expression Of Molecules Involved In the Ctc Cluster Formatio...mentioning
confidence: 99%
“…Labeling of cysteine-free peptides (2,5,7,9) was performed in the presence of 10% ethanol at 95 °C for 30 min. The stock solutions of cysteine-bearing peptides (1,6,8) were prepared in dithiothreitol (DTT, 10 mM final concentration) and radiolabeling was also performed in the presence of 10% ethanol at 75 °C for 30 min. For quality control, an aliquot of 5 μL was withdrawn from the mother solution and diluted in 50 μL of calcium diethylenetriamine pentaacetate (Ca-DTPA) solution.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This compound is used to mobilize hematopoietic stem cells into the peripheral blood for autologous transplantation in cancer patients. Also, elevated CXCR4 expression has been associated with poor disease prognosis, , which suggests imaging and quantification of CXCR4 levels to be clinically relevant for the management of patients with CXCR4-expressing malignancies.…”
Section: Introductionmentioning
confidence: 99%